Creative arts adult education classes qualitiative data - Pearce, E (University of Oxford, 2016)
Qualitative written responses to questions about the effects of attending 7-month-long adult education courses. The method and questions are outlined in Pearce (2016) 'Participants’ perspectives on the social bonding and wellbeing effects of creative arts adult education classes' in the journal Arts & Health. The responses are organised in themes (rather than the question that participants were responding to).